(untitled) (The Review of Diabetic Studies, 2024)
Multidisciplinary collaboration is increasingly recognized as a cornerstone of safe, efficient, and patient-centered hospital care. In Saudi Arabia, hospitals operate within complex service environments shaped by rapid health-system transformation, mass-gathering preparedness, evolving infection prevention expectations, workforce diversification, and heightened attention to patient and staff safety. While collaboration between physicians and nurses has been widely discussed, the integration of public health functions, clinical support services (laboratory, radiology, pharmacy, biomedical engineering, health information management, environmental services), and security services remains under-examined despite its direct influence on outcomes such as infection control, patient flow, incident prevention, and emergency response. This research paper investigates how multidisciplinary collaboration across these three domains improves healthcare delivery in Saudi hospitals and identifies barriers that reduce teamwork effectiveness. Using a mixed-methods conceptual design—combining structured surveys and semi-structured interviews with hospital professionals—this study proposes a practical collaboration framework aligned with hospital governance structures. Key findings emphasize that (1) shared protocols and joint incident reviews reduce avoidable delays and safety events; (2) real-time communication channels and defined escalation pathways strengthen emergency preparedness and reduce crowd-management risks; and (3) collaboration competencies—role clarity, mutual respect, and interdisciplinary leadership—are stronger predictors of service reliability than individual departmental performance alone. The study concludes with an actionable set of governance, workforce, and digital enablement recommendations to institutionalize multidisciplinary collaboration, including multidisciplinary huddles, integrated dashboards, joint training simulations, and standardized interdepartmental service-level agreements.